Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment
By soaking in an acidic solution, the formation of secondary particles with low porosity and high specific surface area, and controlling the pH and sintering conditions during the preparation process, the problems of both cycling performance and energy density of the positive electrode material in the prior art are solved, and high energy density is achieved and a cathode material with excellent circulation performance.
Patent Information
- Application Number
- CN202411392072.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing lithium-rich manganese-based positive electrode materials cannot take into account their circulation performance and volume energy density, and cannot increase the specific surface area to improve the energy density and circulation performance of the battery while maintaining a low porosity.
By soaking the positive electrode active material in an acidic solution, secondary particles with a large specific surface area and low porosity are formed, and the pH and stirring speed of co-precipitation are controlled during the preparation process to form a lithium-rich manganese-based precursor, which is then passed Multiple sintering treatments are used to form a positive electrode active material with excellent circulation properties and high energy density.
It is achieved to increase the specific surface area of the positive electrode active material while maintaining a low porosity, shorten the lithium ion diffusion path, enhance the cycling performance and energy density of the battery, and not destroy the lattice structure.
Smart Images

Figure CN119275279A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular, to positive electrode active materials and preparation methods thereof, positive electrode sheets, batteries, and electrical equipment. Background Art
[0002] Lithium-rich manganese-based positive electrode materials have become a research hotspot in the field of lithium-ion battery positive electrodes due to their high specific capacity and high energy density. Lithium-rich manganese-based positive electrode materials contain Ni, Co, and Mn elements, with a specific capacity of more than 240mAh / g, an average voltage of more than 3.5V, and an energy density higher than layered LiMO2, spinel-type LiMn2O4, and olivine-type LiFePO4. Therefore, lithium-rich manganese-based positive electrode active materials are regarded as the preferred materials for the next generation of lithium-ion battery positive electrode active materials. However, the positive electrode active materials in the related art cannot take into account both their cycle performance and volume energy density. Summary of the invention
[0003] The present application aims to solve one of the technical problems in the related art at least to some extent.
[0004] The first aspect of the present application provides a positive electrode active material, wherein the positive electrode active material is a secondary particle formed by agglomeration of primary particles, wherein the secondary particle has pores, and the BET specific surface area of the positive electrode active material after being immersed in an acidic solution is 1.75 m 2 / g-4m 2 / g, the porosity of the positive electrode active material after being immersed in the acidic solution is 2.6%-6.5%, the weight ratio of the positive electrode active material to the acidic solution is 1:10, the pH of the acidic solution is 5.5, and the immersion time is 2h. Therefore, after the positive electrode active material proposed in the present application is immersed in the acidic solution, the positive electrode active material can have a larger specific surface area while maintaining a lower porosity, thereby improving the energy density and cycle performance of the battery.
[0005] According to some embodiments of the present application, after the secondary particles of the positive electrode active material are immersed in an acidic solution, the average pore size of the pores is 9nm-25nm. Thus, the positive electrode active material can have a larger specific surface area by maintaining a lower porosity, thereby increasing the compaction density of the positive electrode active material.
[0006] According to some embodiments of the present application, the proportion of pores with a pore size less than or equal to 10 nm is 50%-80%, thereby increasing the specific surface area of the positive electrode active material and improving the cycle performance of the battery.
[0007] According to some embodiments of the present application, the compaction density of the positive electrode active material is 2.7 g / cm 3 -3.2g / cm 3. Thus, the energy density of the battery is improved.
[0008] According to some embodiments of the present application, the positive electrode active material satisfies: η=FWHM(104) / FWHM(003), 1.8≤η≤2.8, optionally, 1.85≤η≤2.1, wherein FWHM(104) is the half-peak width of the diffraction peak (104) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (104) is 43.5°-45.5°, and FWHM(003) is the half-peak width of the diffraction peak (003) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (003) is 17.5°-19.5°. Thus, the integrity of the lattice of the positive electrode active material is improved, and the cycle stability of the positive electrode active material is improved.
[0009] According to some embodiments of the present application, the positive electrode active material includes a compound shown in Formula I:
[0010] Li 1+δ (Ni x(1-a) Co y(1-a) Li (1-2x-y)(1-a) / 3 Mn (2-x-y)(1-a) / 3 M 1 a M 2 b ) (2+δ / 2) N n Formula I,
[0011] Among them, 0.02≤δ≤0.08, 0.25≤x≤0.45, 0≤y≤0.1, 0≤a≤0.035, 0≤b≤0.04, 0≤n≤0.04, M 1 Including at least one of Al, Zr, Y, Mg, Ti, W, Si, Yb, Nb, Sc, Ca, La, Sr, Y, M 2 It includes at least one of B, Mg, Al, Ti, V, Sr, Y, Zr, Nb, Mo, Sc, Cr, La, Sr, and W, and N includes at least one of F, S, P, and O.
[0012] According to some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions: 0.03≤δ≤0.06; 0.001≤a≤0.02; 0.001≤b≤0.02; 0≤n≤0.02.
[0013] According to some embodiments of the present application, at least part of the surface of the secondary particles has a coating layer; preferably, the coating layer includes the M 2 Thus, the excessive corrosion of the electrolyte on the positive electrode active material is reduced, and the cycle performance of the battery is improved.
[0014] The second aspect of the present application provides a method for preparing a positive electrode active material, the method comprising: mixing a Ni source, a Co source, a Mn source, a complexing agent, and a precipitant to form a first mixed solution, stirring the first mixed solution, coprecipitating, and drying to obtain a lithium-rich manganese-based precursor, wherein the pH of the first mixed solution is 9-11.5, and the stirring speed is 500rpm-900rpm; mixing the lithium-rich manganese-based precursor, the lithium source, and Mn 1 The first process product is sintered by mixing the first process product and the M 2 The source and the solvent are mixed to form a second mixed liquid, the solid-liquid ratio of the first process product to the solvent is 0.5g / mL-3g / mL, the solid-liquid separation is carried out, and the solid phase material is dried to obtain the second process product; the second process product is sintered for a second time, and the temperature of the second sintering is less than or equal to the temperature of the first sintering to obtain the positive electrode active material.
[0015] Therefore, by making the pH value and stirring speed of the first mixed solution within the above-mentioned range, the primary particles of the positive electrode active material also have good multidirectionality. By controlling the solid-liquid ratio in the process of forming the second mixed solution, the soluble residual substances in the tiny pores between the primary particles can be discharged to the outside of the secondary particles, so that more micropores are formed inside the secondary particles without destroying the lattice structure, thereby obtaining a positive electrode active material with both excellent cycle performance and high volume energy density.
[0016] According to some embodiments of the present application, the solid-to-liquid ratio of the first process product to the solvent is 1.0 g / mL-3 g / mL.
[0017] According to some embodiments of the present application, the method satisfies at least one of the following conditions: the temperature of the second mixed liquid is 5°C-35°C; the first process product, the M 2 The mixing time of the source and the solvent is 30s-1200s, and can be 60s-600s. Thus, micropores can be effectively obtained without destroying the lattice structure of the positive electrode active material.
[0018] According to some embodiments of the present application, 1.12≤n (Li) / (n (Ni) +n (Co) +n (Mn) +n (M1) )≤1.49. Thus, the integrity of the positive electrode active material lattice is improved, and the cycle stability of the positive electrode active material is improved.
[0019] According to some embodiments of the present application, 0≤n (M2) / (n (Ni) +n (Co) +n(Mn) +n (M1) )≤0.04, optionally, 0.001≤n (M2) / (n (Ni) +n (Co) +n (Mn) +n (M1) )≤0.02. Therefore, coating the surface of the positive electrode active material in an appropriate amount can not only reduce the corrosion of the electrolyte to the positive electrode active material and improve the cycle performance, but also increase the conductivity of the secondary particles and increase the capacity of the positive electrode active material.
[0020] According to some embodiments of the present application, the method satisfies at least one of the following conditions: the temperature of the first sintering is T1, and satisfies 800°C≤T1≤980°C; the time of the first sintering is t1, and satisfies 5h≤t1≤15h; the heating rate of the first sintering is V1, and satisfies 1.3°C / min≤V1≤10°C / min. Thus, a better crystal structure can be obtained.
[0021] According to some embodiments of the present application, the method satisfies at least one of the following conditions: the temperature of the second sintering is T2, and satisfies 300°C≤T2≤800°C; the time of the second sintering is t2, and satisfies 6h≤t2≤20h. Thus, a better crystal structure is obtained.
[0022] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the method provided in the second aspect of the present application.
[0023] The fourth aspect of the present application provides a battery, comprising the positive electrode plate provided in the third aspect of the present application.
[0024] The fifth aspect of the present application provides an electrical device, including the battery provided by the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0026] Figure 1 A schematic flow chart of a method for preparing a positive electrode active material according to an embodiment of the present application is shown. DETAILED DESCRIPTION
[0027] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0028] For lithium-rich manganese-based positive electrode active materials, increasing their specific surface area can make the contact between the positive electrode active materials and the electrolyte more complete, promote the interfacial reaction between the positive electrode active materials and the electrolyte, and improve the battery's cycle performance. However, the increase in the specific surface area of lithium-rich manganese-based positive electrode active materials in the related art is accompanied by an increase in porosity. After the porosity increases, the compaction density of the lithium-rich manganese-based positive electrode active materials decreases, sacrificing the battery's energy density. In other words, it is impossible to obtain a lithium-rich manganese-based positive electrode active material with both high energy density and excellent cycle performance.
[0029] The first aspect of the present application provides a positive electrode active material, wherein the positive electrode active material is a secondary particle formed by agglomeration of primary particles, wherein the secondary particle has pores, and the BET specific surface area of the positive electrode active material after being immersed in an acidic solution is 1.75 m 2 / g-4m 2 / g, the porosity of the positive electrode active material after being immersed in the acidic solution is 2.6%-6.5%, the weight ratio of the positive electrode active material to the acidic solution is 1:10, the pH of the acidic solution is 5.5, and the immersion time is 2h.
[0030] During the operation of the battery, the positive electrode active material will be fully infiltrated by the electrolyte, and the interior of the secondary particles will be eroded by the electrolyte, thereby adding new pores inside. The porosity and specific surface area of the positive electrode active material increase with the appearance of new pores. The BET and porosity of the positive electrode active material after being immersed in an acidic solution proposed in this application can truly reflect the properties of the tested material in the electrolyte. This application makes the BET specific surface area and porosity of the positive electrode active material after being immersed in an acidic solution within the above range, which means that during the operation of the battery, after the positive electrode active material is fully infiltrated by the electrolyte, it can have a larger specific surface area while maintaining a low porosity, thereby shortening the diffusion path of lithium ions in the positive electrode active material and increasing the gram capacity of the positive electrode active material.
[0031] The positive electrode active material has a larger specific surface area after being soaked in an acidic solution, which allows the positive electrode active material to be in more complete contact with the electrolyte, promotes the interfacial reaction between the positive electrode active material and the electrolyte, and improves the battery's cycle performance. At the same time, since the porosity of the positive electrode active material remains at a relatively low level after being fully infiltrated by the electrolyte, there is no need to use a smaller compaction density in order to pursue a larger specific surface area for the positive electrode active material during the electrode coating and rolling stages. In other words, the positive electrode active material can have a larger specific surface area during the battery cycle without reducing the compaction density of the positive electrode sheet, thereby obtaining a battery with both excellent cycle performance and higher energy density.
[0032] As an example, the BET specific surface area of the positive electrode active material after being immersed in an acidic solution is 1.75 m 2 / g-4m 2 / g, for example, can be 1.75m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, etc., or may be within the range consisting of any of the above values.
[0033] In the present application, the testing method of BET specific surface area is as follows: the positive electrode active material is immersed in an acidic solution for 2 hours, the weight ratio of the positive electrode active material to the acidic solution is 1:10, the pH of the acidic solution is 5.5, and after the immersion is completed, it is dried at 120°C in a vacuum atmosphere, and the BET specific surface area is measured using a Micromeritics Tristar 3020 surface area analyzer.
[0034] As an example, the porosity of the positive electrode active material after being immersed in the acidic solution can be 2.6%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, etc., or can be a range consisting of any of the above values.
[0035] In the present application, the porosity of the positive electrode active material can be measured by a surface area analyzer of the Tristar 3020 model from Micromeritics.
[0036] According to some embodiments of the present application, the average pore size of the pores after the secondary particles of the positive electrode active material are immersed in an acidic solution is 9nm-25nm. For example, it can be 9nm, 13nm, 17nm, 21nm, 25nm, etc., or it can be a range composed of any of the above values. It can be seen that the average pore size of the positive electrode active material is small, the porosity is small, and the specific surface area is large, so that a positive electrode active material with both high compaction density and better cycle performance can be obtained.
[0037] In the present application, a Tristar 3020 surface area analyzer of Micromeritics was used for testing, and the pore size distribution during desorption was calculated using the BJH method.
[0038] According to some embodiments of the present application, the pore size less than or equal to 10nm accounts for 50%-80%. For example, it can be 50%, 60%, 70% or 80%, or it can be a range composed of any of the above values. The smaller the pore size, the larger the specific surface area of the positive electrode active material. The more small-sized pores there are, the higher the specific surface area of the positive electrode active material can be, the interfacial reaction between the positive electrode active material and the electrolyte can be promoted, and the cycle performance of the battery can be improved.
[0039] It should be noted that the pore size ratio of pores less than or equal to 10 nm refers to the ratio of the sum of the specific surface areas of pores less than or equal to 10 nm in the total specific surface area of the secondary particles.
[0040] According to some embodiments of the present application, the positive electrode active material satisfies: η=FWHM(104) / FWHM(003), 1.8≤η≤2.8, wherein FWHM(104) is the half-peak width of the diffraction peak (104) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (104) is 43.5°-45.5°, and FWHM(003) is the half-peak width of the diffraction peak (003) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (003) is 17.5°-19.5°. For example, η can be 1.8, 2, 2.2, 2.4, 2.6, 2.8, etc., or can be a range consisting of any of the above values.
[0041] The symmetry of the (003) plane in the X-ray diffraction spectrum of the positive electrode material is more obvious than that of the (104) plane. When the ratio of FWHM (104) / FWHM (003) is within the range specified in the present application, it indicates that some Li atoms are distributed in the transition metal layer of the lattice, that is, the Li atoms with a content of (1-2x-y) (1-a) / 3 in Formula I enter the lattice, and the lattice integrity of the positive electrode active material of the present application is better and the cycle stability is better. According to some specific embodiments of the present application, 1.85≤η≤2.1.
[0042] In the present application, FWHM (104) and FWHM (003) can be obtained by testing with a Smart Lab 9KW X-ray diffractometer of Rigaku Corporation.
[0043] According to some embodiments of the present application, the compaction density of the positive electrode active material can be 2.7 g / cm 3 -3.2g / cm 3 For example, it can be 2.7 g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 、3.1g / cm 3 、3.2g / cm 3 The energy density of the battery is thereby increased.
[0044] According to some embodiments of the present application, the compaction density of the positive electrode active material can be obtained by testing with a Japanese Mitsubishi powder impedance measurement system.
[0045] According to some embodiments of the present application, the positive electrode active material includes a compound shown in Formula I:
[0046] Li 1+δ (Ni x(1-a) Co y(1-a) Li (1-2x-y)(1-a) / 3 Mn (2-x-y)(1-a) / 3 M 1 a M 2 b ) (2+δ / 2) N n Formula I,
[0047] Among them, 0.02≤δ≤0.08, 0.25≤x≤0.45, 0≤y≤0.1, 0≤a≤0.035, 0≤b≤0.04, 0≤n≤0.04, M 1 Including at least one of Al, Zr, Y, Mg, Ti, W, Si, Yb, Nb, Sc, Ca, La, Sr, Y, M 2 It includes at least one of B, Mg, Al, Ti, V, Sr, Y, Zr, Nb, Mo, Sc, Cr, La, Sr, and W, and N includes at least one of F, S, P, and O.
[0048] As an example, δ may be 0.002, 0.004, 0.006, 0.008, etc., or may be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.03≤δ≤0.06.
[0049] As an example, x may be 0.25, 0.3, 0.35, 0.4, 0.45, etc., or may be a range consisting of any of the above values.
[0050] As an example, y may be 0, 0.03, 0.05, 0.07, 0.1, etc., or may be a range consisting of any of the above values.
[0051] As an example, a may be 0, 0.01, 0.02, 0.03, 0.035, etc., or may be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.001≤a≤0.02.
[0052] As an example, b can be 0, 0.01, 0.02, 0.03, 0.04, etc., or can be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.001≤b≤0.02.
[0053] As an example, n can be 0, 0.005, 0.01, 0.015, 0.02, etc., or can be a range consisting of any of the above values. According to some specific embodiments of the present application, 0≤n≤0.02.
[0054] The second aspect of the present application provides a method for preparing a positive electrode active material, the method comprising: mixing a Ni source, a Co source, a Mn source, a complexing agent, and a precipitant to form a first mixed solution, stirring the first mixed solution, coprecipitating, and drying to obtain a lithium-rich manganese-based precursor, wherein the pH of the first mixed solution is 9-11.5, and the stirring speed is 500rpm-900rpm; mixing the lithium-rich manganese-based precursor, the lithium source, and Mn 1 The first process product is sintered by mixing the first process product and the M 2 The first process product is mixed with a source and a solvent to form a second mixed solution, the solid-liquid ratio of the first process product to the solvent is 0.5g / mL-3g / mL, the solid-liquid separation is carried out, and the solid phase material is dried to obtain the second process product; the second process product is subjected to a second sintering, and the temperature of the second sintering is less than or equal to the temperature of the first sintering, to obtain the positive electrode active material. Thus, by controlling the pH and rotation speed of the coprecipitation process and the solid-liquid ratio in the process of forming the second mixed solution, the soluble residual substances in the tiny pores between the primary particles can be discharged to the outside of the secondary particles, so that more micropores are formed inside the secondary particles, while the lattice structure is not destroyed, thereby obtaining a positive electrode active material with both excellent cycle performance and high volume energy density.
[0055] The following is a detailed description of this method, see Figure 1 , the method comprising:
[0056] S10: Mixing a Ni source, a Co source, a Mn source, a complexing agent, and a precipitant to form a first mixed solution, stirring the first mixed solution, co-precipitating, and drying to obtain a lithium-rich manganese-based precursor.
[0057] According to some embodiments of the present application, a Ni source, a Co source, a Mn source, a complexing agent, and a precipitant are mixed to form a first mixed solution, and a slurry is obtained by co-precipitation. The slurry is sequentially aged, filter-pressed, and dried to obtain a lithium-rich manganese-based precursor.
[0058] According to some embodiments of the present application, the precipitant includes at least one of NaOH, KOH, and LiOH.
[0059] According to some embodiments of the present application, the pH of the first mixed solution may be 9-11.5, for example, 9, 9.5, 10, 10.5, 11, 11.5, etc., or may be a range consisting of any of the above values.
[0060] According to some embodiments of the present application, the stirring rotation speed may be 500 rpm-900 rpm, for example, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, etc., or may be a range consisting of any of the above numerical values.
[0061] By making the pH value and stirring speed of the first mixed liquid within the above range, the lithium-rich manganese-based precursor has both good multi-directionality and high tap density, so that the primary particles of the positive electrode active material also have good multi-directionality. During the battery cycle, the positive electrode active material can obtain more micropores after being immersed in the electrolyte, that is, the positive electrode active material can have a larger specific surface area when the porosity is increased less, thereby obtaining a battery with both excellent cycle performance and high energy density.
[0062] According to some embodiments of the present application, the temperature during the coprecipitation reaction may be 50°C-80°C, for example, 50°C, 60°C, 70°C, 80°C, etc., or may be a range consisting of any of the above values.
[0063] According to some embodiments of the present application, the coprecipitation reaction time is 30h-100h, for example, it can be 30h, 50h, 70h, 90h, 100h, etc., or can be a range consisting of any of the above numerical values.
[0064] S20: mixing the lithium-rich manganese-based precursor, lithium source, M 1 The source is mixed and sintered for the first time to obtain a first process product. According to some embodiments of the present application, the lithium source may include at least one of lithium carbonate and lithium hydroxide.
[0065] According to some embodiments of the present application, the M1 Sources include M 1 Oxide, M 1 Sulfide, M 1 Fluoride, M 1 Hydroxide, M 1 at least one of the carbonates.
[0066] According to some embodiments of the present application, 0≤n (M1) / (n (Ni) +n (Co) +n (Mn) )≤0.04, for example, it can be 0, 0.01, 0.02, 0.03, 0.04, etc., or can be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.001≤n (M1) / (n (Ni) +n (Co) +n (Mn) )≤0.02.
[0067] According to some embodiments of the present application, the heating rate V1 of the first sintering may satisfy 1.3°C / min≤V1≤10°C / min, for example, it may be 1.3°C / min, 3°C / min, 6°C / min, 8°C / min, 10°C / min, etc., or it may be a range consisting of any of the above values.
[0068] According to some embodiments of the present application, the temperature of the first sintering is T1 and satisfies 800℃≤T1≤980℃. For example, it can be 800℃, 840℃, 880℃, 920℃, 960℃, 980℃, etc., or can be a range consisting of any of the above numerical values.
[0069] According to some embodiments of the present application, the time of the first sintering is t1, satisfying 5h≤t1≤15h. For example, it can be 5h, 7h, 9h, 11h, 13h, 15h, etc., or can be a range consisting of any of the above values.
[0070] Thus, by setting T1, V1, and t1 of the first sintering to the above ranges, primary particles can be generated uniformly and simultaneously, thereby obtaining a larger number of microporous structures between the primary particles.
[0071] According to some embodiments of the present application, 1.12≤n (Li) / (n (Ni) +n (Co) +n (Mn) +n (M1) )≤1.49. Thus, the integrity of the positive electrode active material lattice is improved, and the cycle stability of the positive electrode active material is improved. Wherein, n is the molar amount of the corresponding element.
[0072] As an example, n (Li) / (n (Ni) +n (Co) +n (Mn) +n (M1) ) can be 1.12, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.49, etc., or can be a range consisting of any of the above values. Wherein, n is the molar amount of the corresponding element.
[0073] S30: The first process product, M 2 The first process product and the solvent are mixed to form a second mixed solution, the solid-liquid ratio of the first process product to the solvent is 0.5g / mL-3g / mL, the solid-liquid separation is performed, and the solid phase substance is dried to obtain the second process product
[0074] According to some embodiments of the present application, the first process product, M 2 The sources are sequentially added into the aqueous solution to form a second mixed solution, and solid-liquid separation is performed to obtain a solid phase substance, and the solid phase substance is dried to obtain a second process product.
[0075] It should be noted that when there is no M in the positive electrode active material 2 If the element is 2 source.
[0076] According to some embodiments of the present application, the solid-to-liquid ratio of the first process product to the solvent can be 0.5 g / mL, 1 g / mL, 1.5 g / mL, 2 g / mL, 2.5 g / mL, 3 g / mL, etc., or can be a range consisting of any of the above numerical values.
[0077] According to some specific embodiments of the present application, the solid-to-liquid ratio of the first process product to the solvent is 1.0 g / mL-3 g / mL.
[0078] According to some embodiments of the present application, the temperature of the second mixed liquid may be 5° C.-35° C. For example, it may be 5° C., 10° C., 15° C., 20° C., 25° C., 30° C., 35° C., etc., or may be a range consisting of any of the above values.
[0079] According to some embodiments of the present application, the first process product, the M 2 The mixing time of the first process product, the M 2 The mixing time of the source and the solvent is 60s-600s.
[0080] Thus, by setting the solid-liquid ratio, the temperature of the second mixed liquid and the mixing time within the above ranges, the fillers in the micropores between the primary particles are washed out and discharged to the outside of the secondary particles without destroying the crystal structure.
[0081] According to some embodiments of the present application, 0≤n (M2) / (n (Ni) +n (Co) +n (Mn) +n (M1) )≤0.04, for example, it can be 0, 0.01, 0.02, 0.03, 0.04, etc., or can be a range consisting of any of the above values. According to some specific embodiments of the present application, 0.001≤n (M2) / (n (Ni) +n (Co) +n (Mn) +n (M1) )≤0.02. Where n is the molar amount of the corresponding element.
[0082] According to some embodiments of the present application, the M 2 Sources include M 2 Oxide, M 2 Sulfide, M 2 Fluoride, M 2 Hydroxide, M 2 Carbonate, M 2 At least one of the oxyhydroxides.
[0083] S40: performing a second sintering on the second process product, wherein the temperature of the second sintering is less than or equal to the temperature of the first sintering, so as to obtain the positive electrode active material
[0084] According to some embodiments of the present application, the second process product is sintered for a second time in an oxygen-containing atmosphere, and the sintered product is screened and iron-removed to obtain the positive electrode active material.
[0085] According to some embodiments of the present application, the temperature of the second sintering is T2 and satisfies 300℃≤T2≤800℃. For example, it can be 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, etc., or can be a range consisting of any of the above numerical values.
[0086] According to some embodiments of the present application, the second sintering time is t2, and satisfies 6h≤t2≤20h. For example, it can be 6h, 10h, 14h, 18h, 20h, etc., or can be a range consisting of any of the above values.
[0087] Therefore, by setting the temperature and time of the second sintering within the above range, the pore structure in the secondary particles can be better preserved, reducing the risk of closed pores after re-sintering of the primary particles.
[0088] In summary, the positive electrode active material proposed in this application has the following advantages:
[0089] (1) After the positive electrode active material provided in the present application contacts with the electrolyte, it can have a larger specific surface area while maintaining a lower porosity, thereby shortening the diffusion path of lithium ions in the positive electrode active material and increasing the gram capacity of the positive electrode active material.
[0090] (2) Since the positive electrode active material has a large specific surface area, the positive electrode active material can be fully in contact with the electrolyte, promoting the interfacial reaction between the positive electrode active material and the electrolyte and improving the cycle performance of the battery.
[0091] (3) After the simulated electrolyte infiltration process, the average pore size of the positive electrode active material is small. These small pore sizes enable the positive electrode active material to have a larger specific surface area under the condition of lower porosity, thereby obtaining a positive electrode active material with both higher compaction density and excellent cycle performance.
[0092] (4) In the process of preparing the lithium-rich manganese-based precursor, the present application controls the pH value and stirring speed of the first mixed solution so that the lithium-rich manganese-based precursor has both good multi-directionality and high tap density, thereby making the primary particles of the positive electrode active material also have good multi-directionality. During the battery cycle, the positive electrode active material can obtain more micropores after being immersed in the electrolyte, that is, the positive electrode active material can have a larger specific surface area when the porosity is increased less, thereby obtaining a battery with both excellent cycle performance and high energy density.
[0093] (5) In the process of preparing the positive electrode active material, the present application controls the solid-liquid ratio of the first process product and the solvent, so that the soluble residual substances in the tiny pores between the primary particles can be discharged to the outside of the secondary particles during the formation of the second process product, thereby forming more micropores inside the secondary particles without destroying the lattice structure, thereby obtaining a positive electrode active material with both excellent cycle performance and high volume energy density.
[0094] (6) The positive electrode active material proposed in this application has good lattice integrity, which can further improve the cycle performance of the battery.
[0095] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the method provided in the second aspect of the present application.
[0096] The fourth aspect of the present application provides a battery, comprising the positive electrode sheet provided in the third aspect of the present application. Thus, the battery has a higher volume energy density and cycle performance.
[0097] The fifth aspect of the present application provides an electrical device, including the battery provided by the fourth aspect of the present application.
[0098] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0099] Example 1
[0100] 1. Preparation of positive electrode active materials
[0101] (1) Under nitrogen protection, nickel sulfate, cobalt sulfate, manganese sulfate (molar ratio Ni: Co: Mn = 33: 5: 62), 25% ammonia water, and a precipitant are introduced into a reactor in parallel to carry out a coprecipitation reaction. The precipitant is a 2 mol / L NaOH aqueous solution. The coprecipitation reaction temperature is 60° C., the rotation speed is 550 rpm, the time is 50 h, the pH is 10.2, and the mixture is naturally cooled to room temperature, crushed, and sieved to obtain a lithium-rich manganese-based precursor;
[0102] (2) mixing the lithium-rich manganese-based precursor, lithium carbonate and TiO2, and performing the first sintering, the sintering atmosphere is air, the heating rate V1=5°C / min, t1=10h, T1=880°C, and naturally cooling to room temperature, then crushing and sieving to obtain the first process product;
[0103] (3) Mixing the first process product with deionized water and AlF to form a second mixed solution, the solid-liquid ratio of the first process product to deionized water is 2 g / mL, the temperature of the second mixed solution is 12° C., the mixing time is 300 s, and the second process product is obtained by filter pressing and vacuum drying;
[0104] (4) The second process product is sintered for the second time in an air atmosphere at T2 = 440 ° C, t2 = 8 h, and then sieved and iron removed, and naturally cooled to room temperature to obtain Li 1.05 (Ni 0.286 Co 0.043 Li 0.126 Mn 0.538 Ti 0.007 )Al 0.012 O 2.025 F 0.012 .
[0105] 2. Preparation of positive electrode sheet
[0106] The positive electrode active material Li prepared in Example 1 1.05 (Ni 0.286 Co 0.043 Li 0.126 Mn 0.538 Ti 0.007 )Al 0.012 O 2.025 F 0.012 , polyvinylidene fluoride (PVDF), and acetylene black are mixed with an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 90:5:5 to form a uniform slurry, the slurry is coated on an aluminum foil and dried, and then stamped into a positive electrode sheet with a diameter of 12 mm and a thickness of 120 μm at a pressure of 100 MPa, and then the positive electrode sheet is placed in a vacuum drying oven at 120°C and dried for 12 hours.
[0107] 3. Preparation of negative electrode sheet
[0108] The negative electrode uses a Li metal sheet with a diameter of 17 mm and a thickness of 1 mm.
[0109] 4. Isolation film
[0110] A polyethylene porous membrane with a thickness of 25 μm.
[0111] 5. Electrolyte
[0112] An equal volume mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1 mol / L LiPF6 as the electrolyte.
[0113] 6. Assemble the battery
[0114] The positive electrode plate, the isolation membrane, the negative electrode plate and the electrolyte were assembled into a 2025 type button battery in an Ar gas glove box with a water content and an oxygen content both less than 5 ppm.
[0115] The processes for preparing the positive electrode active materials in Examples 2 to 9 and Comparative Examples 1 to 3 are shown in Table 1. The method for preparing a battery using the positive electrode active materials is the same as in Example 1. The differences are detailed in Table 1.
[0116]
[0117]
[0118] Comparative Example 1
[0119] The preparation process of the positive electrode active material is the same as that of Example 1, except that the pH of the first mixed solution is 9.0 and the rotation speed is 400 rpm.
[0120] Comparative Example 2
[0121] The preparation process of the positive electrode active material is the same as that of Example 1, except that the pH of the first mixed solution is 11.8 and the rotation speed is 950 rpm.
[0122] Comparative Example 3
[0123] The preparation process of the positive electrode active material is the same as that of Example 1, except that the solid-to-liquid ratio of the first process product to deionized water is 5 g / mL.
[0124] Performance Testing
[0125] 1.BET specific surface area
[0126] In the present application, the testing method of BET specific surface area is: soaking the positive electrode active material in an acidic solution for 2 hours, the weight ratio of the positive electrode active material to the acidic solution is 1:10, the pH of the acidic solution is 5.5, and after soaking, drying at 120°C in a vacuum atmosphere, and testing is performed using Micromeritics' Tristar 3020 surface area analyzer.
[0127] 2. Porosity
[0128] The pore volume was obtained by using a Micromeritics Tristar 3020 surface area analyzer, and the skeleton volume was obtained by using a Micromeritics AccuPyc 1345 density analyzer. Porosity = pore volume / (pore volume + skeleton volume) × 100%
[0129] 3. Average pore size
[0130] The surface area was measured by using the Micromeritics Tristar 3020 surface area analyzer.
[0131] 4. The proportion of pores with a diameter less than or equal to 10 nm
[0132] The pore size distribution was obtained by using a Micromeritics Tristar 3020 surface area analyzer, wherein the pore size ratio was less than or equal to 10 nm.
[0133] 5. Compacted density
[0134] Obtained through testing by Japan Mitsubishi powder impedance measurement system.
[0135] 6.XRD
[0136] The results were obtained by using a Smart Lab 9KW X-ray diffractometer from Rigaku Corporation, where the FWHM of the (003) peak was calculated to have a 2θ value of 17.5°-19.5°, and the FWHM of the (104) peak was calculated to have a 2θ value of 43.5°-45.5°.
[0137] 7. First discharge specific capacity
[0138] The initial discharge specific capacity is obtained by placing the button battery for 2 hours after production. After the open circuit voltage stabilizes, the positive electrode is charged to a cut-off voltage of 4.55V at a current density of 25mA / g, and the constant voltage charging cut-off current is 0.05C. Subsequently, the battery is discharged at the same current density to a cut-off voltage of 2.5V, thus obtaining the first discharge specific capacity.
[0139] 8. Average discharge voltage
[0140] Average discharge voltage = discharge energy during discharge / discharge capacity during discharge.
[0141] 9. Volumetric energy density
[0142] Volume energy density = compaction density of powder × first discharge specific capacity × average discharge voltage.
[0143] 10. Cycle capacity retention rate
[0144] After the button battery is discharged for the first time, it is charged and discharged at 0.1C twice, and the current density of the positive electrode is changed to 250mAh / g, the charging cut-off voltage is 4.55V, and the constant voltage charging cut-off current is 0.05C. Then, it is discharged at the same current density to the cut-off voltage of 2.5V, and the first cycle capacity is obtained. After 50 cycles, the 50th cycle capacity is obtained. Cycle capacity retention rate = 50th cycle capacity / first cycle capacity × 100%.
[0145] The test results of the positive electrode active materials and batteries in Examples 1 to 9 and Comparative Examples 1 to 3 are shown in Table 2.
[0146]
[0147]
[0148] It can be seen from the comparison between Examples 1 to 9 and Comparative Examples 1 to 3 that in the process of preparing the positive electrode active material, the pH of the first mixed solution, the stirring speed and the solid-liquid ratio of the first process product to the solvent are controlled. After the positive electrode active material is soaked in an acidic solution, the average pore size of the positive electrode active material is small, and the proportion of pores less than 10 nm is large, so that the positive electrode active material has a smaller porosity and a larger BET specific surface area, and the first discharge specific capacity, average discharge voltage, volume energy density and cycle capacity retention rate of the battery are all high, indicating that the positive electrode active material proposed in the present application can not only improve the volume energy density of the battery, but also make the positive electrode active material more fully contact with the electrolyte during the battery charging and discharging process, thereby promoting the interfacial reaction between the positive electrode active material and the electrolyte, and improving the cycle performance of the battery.
[0149] It can be seen from the comparison between Example 1 and Comparative Example 1 that if the stirring speed is too low, although the specific surface area of the positive electrode active material is large, its porosity is also large, resulting in a low volume energy density of the battery.
[0150] It can be seen from the comparison between Example 1 and Comparative Example 2 that if the stirring speed is too high, the BET specific surface area and porosity of the positive electrode active material are both small, resulting in a low first discharge capacity of the battery.
[0151] It can be seen from the comparison between Example 1 and Comparative Example 3 that if the solid-liquid ratio of the first process product and the solvent is too large, the BET specific surface area and porosity of the positive electrode active material are both large, and a battery with high volume energy density, first discharge specific capacity and cycle capacity retention rate cannot be obtained.
[0152] It can be seen from Examples 1, 7 to 9 that in the process of preparing the positive electrode active material, by adjusting the amount of lithium source added (i.e., n (Li) / (n (Ni) +n (Co) +n (Mn) +n (M1) )), the Li content in the positive electrode active material can be regulated, and then the FWHM(104) / FWHM(003) ratio can be controlled to obtain a positive electrode active material with better lattice integrity, thereby improving the battery's cycle capacity retention rate.
[0153] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material is a secondary particle formed by agglomeration of primary particles, the secondary particle has pores, and the BET specific surface area of the positive electrode active material after being immersed in an acidic solution is 1.75 m 2 / g-4m 2 / g, the porosity of the positive electrode active material after being immersed in the acidic solution is 2.6%-6.5%, the weight ratio of the positive electrode active material to the acidic solution is 1:10, the pH of the acidic solution is 5.5, and the immersion time is 2h.
2. The positive electrode active material according to claim 1, characterized in that After the secondary particles of the positive electrode active material are immersed in an acidic solution, the average pore diameter of the pores is 9nm-25nm.
3. The positive electrode active material according to claim 2, characterized in that The pores with a pore diameter less than or equal to 10 nm account for 50%-80%.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The compaction density of the positive electrode active material is 2.7 g / cm 3 -3.2g / cm 3 .
5. The positive electrode active material according to claim 4, characterized in that The positive electrode active material satisfies: η=FWHM(104) / FWHM(003), 1.8≤η≤2.8, optionally, 1.85≤η≤2.1, wherein FWHM(104) is the half-peak width of the diffraction peak (104) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (104) is 43.5°-45.5°, and FWHM(003) is the half-peak width of the diffraction peak (003) of the X-ray diffraction spectrum, and the 2θ value corresponding to the diffraction peak (003) is 17.5°-19.5°.
6. The positive electrode active material according to claim 1, characterized in that The positive electrode active material includes a compound shown in Formula I: Li 1+δ (Ni x(1-a) Co y(1-a) Li (1-2x-y)(1-a) / 3 Mn (2-x-y)(1-a) / 3 M 1 a M 2 b )O (2+δ / 2) N n Formula I, Among them, 0.02≤δ≤0.08, 0.25≤x≤0.45, 0≤y≤0.1, 0≤a≤0.035, 0≤b≤0.04, 0≤n≤0.04, M 1 Including at least one of Al, Zr, Y, Mg, Ti, W, Si, Yb, Nb, Sc, Ca, La, Sr, Y, M 2 It includes at least one of B, Mg, Al, Ti, V, Sr, Y, Zr, Nb, Mo, Sc, Cr, La, Sr, and W, and N includes at least one of F, S, P, and O.
7. The positive electrode active material according to claim 6, characterized in that Satisfy at least one of the following conditions: 0.03≤δ≤0.06; 0.001≤a≤0.02; 0.001≤b≤0.02; 0≤n≤0.02。 8. The positive electrode active material according to claim 6, characterized in that At least part of the surface of the secondary particles has a coating layer; preferably, the coating layer includes the M 2 element.
9. A method for preparing a positive electrode active material, characterized in that: include: A Ni source, a Co source, a Mn source, a complexing agent, and a precipitant are mixed to form a first mixed solution, and the first mixed solution is stirred, co-precipitated, and dried to obtain a lithium-rich manganese-based precursor, wherein the pH of the first mixed solution is 9-11.5, and the stirring speed is 500 rpm-900 rpm; The lithium-rich manganese-based precursor, lithium source, M 1 The source mixture is mixed and sintered for the first time to obtain a first process product; The first process product, M 2 The first process product and the solvent are mixed to form a second mixed solution, the solid-liquid ratio of the first process product to the solvent is 0.5 g / mL-3 g / mL, the solid-liquid is separated, and the solid phase is dried to obtain a second process product; The second process product is subjected to a second sintering, wherein the temperature of the second sintering is less than or equal to the temperature of the first sintering, so as to obtain the positive electrode active material.
10. The method according to claim 9, characterized in that The solid-to-liquid ratio of the first process product to the solvent is 1.0 g / mL-3 g / mL.
11. The method according to claim 9, characterized in that Satisfy at least one of the following conditions: The temperature of the second mixed liquid is 5°C-35°C; The first process product, the M 2 The mixing time of the source and the solvent is 30s-1200s, and can be optionally 60s-600s.
12. The method according to claim 9, characterized in that 1.12≤n (Li) / (n (Ni) +n (Co) +n (Mn) +n (M1) )≤1.49。 13. The method according to claim 9, characterized in that 0≤n (M2) / (n (Ni) +n (Co) +n (Mn) +n (M1) )≤0.04, optionally, 0.001≤n (M2) / (n (Ni) +n (Co) +n (Mn) +n (M1) )≤0.
02.
14. The method according to claim 9, characterized in that Satisfy at least one of the following conditions: The temperature of the first sintering is T1, and satisfies 800°C≤T1≤980°C; The first sintering time is t1, which satisfies 5h≤t1≤15h; The heating rate of the first sintering is V1, and satisfies 1.3°C / min≤V1≤10°C / min.
15. The method according to claim 9, characterized in that Satisfy at least one of the following conditions: The temperature of the second sintering is T2, and satisfies 300°C≤T2≤800°C; The second sintering time is t2, and satisfies 6h≤t2≤20h.
16. A positive electrode plate, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 8 or the positive electrode active material prepared by the method according to any one of claims 9 to 15.
17. A battery, characterized in that: Including the positive electrode sheet as described in claim 16.
18. An electrical equipment, characterized in that: Comprising the battery of claim 17.